2012
DOI: 10.5539/elt.v5n12p87
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Language Teaching: Possibilities and Problems

Abstract: This paper investigates the teaching of English at undergraduate colleges in the state of Andhra Pradesh, India in the backdrop of Andhra Pradesh English Lecturers' Retraining Program. The program was jointly sponsored and conducted by the Directorate of Collegiate Education, Government of AP and the US State Department English Language Fellow Program. The main aim of the program was to update the teaching skills of English teachers of undergraduate colleges in the State. The program trained teachers to adopt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…In the same study, teachers also confirmed this situation and emphasized that there was always a deficiency in speaking skills, even though they did not experience any difficulties in developing other skills of the students. On the other hand, teachers' intensive use of communicative activities also played an important role in the development of students' listening, writing and reading skills (Sreehari, 2012). The results obtained from the students' responses about how the speaking activities were performed showed that these activities were generally in the form of animating ready-made dialogues or question-and-answer rather than the speeches that students constructed.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, teachers also confirmed this situation and emphasized that there was always a deficiency in speaking skills, even though they did not experience any difficulties in developing other skills of the students. On the other hand, teachers' intensive use of communicative activities also played an important role in the development of students' listening, writing and reading skills (Sreehari, 2012). The results obtained from the students' responses about how the speaking activities were performed showed that these activities were generally in the form of animating ready-made dialogues or question-and-answer rather than the speeches that students constructed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there are problems associated with CLT . Among these problems, researchers (Kumaradivelu 1994(Kumaradivelu , 2006Sreehari 2012) highlight its colonial or imperialistic background . The success of CLT is partly due to the rapid spread of textbooks .…”
Section: The Communicative Method or Communicative Language Teachingmentioning
confidence: 99%
“…listening, speaking, reading and writing as required. Yet, teachers should play a significant role in facilitating language learning in meaningful ways (Sreehari, 2012).…”
Section: ) Argue Thatmentioning
confidence: 99%